O componente curricular Projeto de Vida como experiência formativa em uma escola cidadã integral no município de João Pessoa – PB - Santos, Flávia Melina Azevedo Vaz dos (2021)
This research is part of studies on Integral Education experiences in Brazil, specifically the implementation of Integral Citizen Schools (ECI's) in Paraíba in 2016, becoming a Comprehensive Education Program in 2018. In this sense, high school has undergone new arrangements curriculum, including the Life Project component, which in Paraíba is seen a central aspect in the pedagogical model of ECI's. In this way, we have as central objective to analyze how the Life Project is constituted as a didactic-curricular device of formative experiences in the Integral Citizen School, starting from the following problems: what the regulatory documents of national and local educational policies specify about Integral Education and the Life Project component? What are the evaluations of young people regarding experiences lived in the Life Project? Theoretical discussions are guided by the historical dimension of Integral Education (GADOTTI 2009; CAVALIERE, 2002, 2010; MOLL, 2012); construction of high school for youth (DAYRELL, 2003; 2007; 2014; ARROYO, 2012; 2014); pedagogical dimensions of the Life Project (State Guidelines, 2018, 2019,2020; ICE, 2016a; 2016b; 2016c) and the technical guidelines of Educational Policies for Secondary Education (DCNEM, 2012; PNE, 2014; New High School, 2017; BNCC, 2018). We will use the qualitative approach, as it allows the investigation of elements that constitute human relationships. We have as a research method the Grounded Theory, according to the guidelines of Charmaz (2009), under the understanding that this theory allows the collection of data and its analysis serves as a guiding thread for the organization of conceptual arguments since the beginning of the research, building, simultaneously, theoretical structuring based on empirical data. It was possible to verify the acceptance by young people about changes in the curriculum, while they were at school. During the interruption of face-to-face activities due to the pandemic, they demonstrate their homesickness for daily contact with colleagues and school staff. The pandemic had a profound impact on school dynamics and teaching in the Life Project component. We identified the emphasis on technical training, neoliberal and children's trends in the curriculum guidelines for this component. In remote education, were scorned the disciplines of the diversified base, to the detriment of giving evidence to the contents of the common base, with a view to the results of ENEM, which scarred the Life Project. The importance of other educational times and spaces was demonstrated, that is why we point out the Integrated Pedagogy as a theoretical and methodological basis to reinforce the gaps left with emphasis on the concept of plural learning and youth.